Human Papillomavirus (HPV) vaccination practices and associated factors among female adolescent students in Eastern Zone of Tigray, Northern Ethiopia, 2024 - Tesfay Berhe Teka; Haftom Legese; Tsige Shishay; Meresa Berwo Mengesha; Haftay Gebremedhin (Therapeutic Advances in Vaccines and Immunotherapy)
Background: Human papillomavirus (HPV) continues to pose a significant threat to public health, serving as the primary cause of cervical cancer. To address this issue, a vaccine has been developed to decrease the incidence of cervical cancer. However, the practice and its associated factors with the uptake of the vaccine have not been well studied in this particular region. Consequently, this study aims to evaluate the practice of HPV vaccination and its associated factors among female adolescent students in the Eastern Zone of Tigray, North Ethiopia, 2024. Methods: A cross-sectional study design was conducted from September 2023 to January 2024 at primary schools of the Eastern Zone, Tigray, Ethiopia. Data related to HPV vaccination practice and its associated factors were collected from 634 female adolescent primary school students. The collected data were checked for completeness daily, coded, entered, and cleaned using Epinfo version 7.2.3 then exported and analyzed using SPSS version 24. Bivariate and multivariate logistic regression analyses were used to assess the association between dependent and independent variables. The corresponding variables with a p -value ( p  < 0.05) with a 95% confidence interval were considered statistically significant. Result: Among the 634 participants, 61.7% received the quadrivalent Gardasil HPV vaccine. Of these, 52.1% (330/634) demonstrated good knowledge, with an adjusted odds ratio (AOR) of 1.931 (95% confidence interval (CI), 1.364–2.735) and a p -value < 0.000. Moreover, participants who had a positive attitude toward HPV vaccination, with (AOR = 1.529, 95% CI = 1.049–2.230; p -value < 0.027) and participants who expressed their agreement for taking the HPV vaccine (AOR = 1.816, 95% CI = 1.046–3.152; p -value < 0.034) were factors associated with female adolescent students’ practice of the HPV vaccination. Conclusion and recommendation: The results indicated that the majority of study participants received one dose of the HPV vaccine. The study further reveals several factors associated with HPV vaccination among female adolescent students, including a positive attitude toward the vaccine and good knowledge about its benefits. Health authorities are recommended to promote the HPV vaccine through mass media in schools, religious institutions, and healthcare facilities to increase practice among adolescent females.